Seasonally different carbon flux changes in the Southern Ocean in response to the southern annular mode - Hauck, J.; Voelker, C.; Wang, T.; Hoppema, M.; Losch, M.; Wolf-gladrow, D. A. (Global Biogeochemical Cycles, 2013)
Stratospheric ozone depletion and emission of greenhouse gases lead to a trend of the southern annular mode (SAM) toward its high-index polarity. The positive phase of the SAM is characterized by stronger than usual westerly winds that induce changes in the physical carbon transport. Changes in the natural carbon budget of the upper 100 m of the Southern Ocean in response to a positive SAM phase are explored with a coupled ecosystem-general circulation model and regression analysis. Previously overlooked processes that are important for the upper ocean carbon budget during a positive SAM period are identified, namely, export production and downward transport of carbon north of the polar front (PF) as large as the upwelling in the south. The limiting micronutrient iron is brought into the surface layer by upwelling and stimulates phytoplankton growth and export production but only in summer. This leads to a drawdown of carbon and less summertime outgassing (or more uptake) of natural CO2. In winter, biological mechanisms are inactive, and the surface ocean equilibrates with the atmosphere by releasing CO2. In the annual mean, the upper ocean region south of the PF loses more carbon by additional export production than by the release of CO2 into the atmosphere, highlighting the role of the biological carbon pump in response to a positive SAM event.